1993
DOI: 10.1002/neu.480241202
|View full text |Cite
|
Sign up to set email alerts
|

Influences of neurotrophins on mammalian motoneurons in vivo

Abstract: Several recently reported investigations have shown that a member of the neurotrophin family of neuronal growth factors, brain-derived neurotrophic factor (BDNF), supports motoneurons in vitro and rescues motoneurons from naturally occurring and axotomy-induced cell death (Oppenheim et al., 1992b; Sendtner et al., 1992b; Yan et al., 1992; Koliatsos et al., 1993; Henderson et al., 1993). In the current study, we have explored the issue of whether BDNF and other neurotrophins act to regulate motoneuron survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
136
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 109 publications
14
136
1
Order By: Relevance
“…Neurotrophin-3 knockout experiments have noted no loss of MNs in the LMC and MMC (Yan et al, 1993;Snider, 1994;Huang and Reichardt, 2001;Patel et al, 2003) and facial motor nucleus neuron loss is shown to be nonsignificant, i.e., no obvious deficits were detected, in the brainstem of newborn NT-3Ϫ/Ϫ mice . Whereas certain in vitro studies have demonstrated inadequate promotion of chick motoneuron survival through the use of NT-3 and BDNF, the application of these same neurotrophic factors on cultured fetal rat motoneurons demonstrated a survival-promoting effect for these agents (reviewed in Li et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Neurotrophin-3 knockout experiments have noted no loss of MNs in the LMC and MMC (Yan et al, 1993;Snider, 1994;Huang and Reichardt, 2001;Patel et al, 2003) and facial motor nucleus neuron loss is shown to be nonsignificant, i.e., no obvious deficits were detected, in the brainstem of newborn NT-3Ϫ/Ϫ mice . Whereas certain in vitro studies have demonstrated inadequate promotion of chick motoneuron survival through the use of NT-3 and BDNF, the application of these same neurotrophic factors on cultured fetal rat motoneurons demonstrated a survival-promoting effect for these agents (reviewed in Li et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Neurotrophin-3, like other neurotrophins of the same family, binds to the low affinity p75 NTR receptor protein (where NTR ϭ neurotrophin receptor; Yan et al, 1993). The highaffinity receptor most commonly associated with NT-3 is the tyrosine kinase TrkC receptor, although NT-3 is known to interact with both TrkA and TrkB in certain cell culture systems (Barbacid, 1994;Snider, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations